2021
DOI: 10.1089/jmf.2020.4838
|View full text |Cite
|
Sign up to set email alerts
|

AqueousAzadirachta indica(Neem) Extract Attenuates Insulin Resistance to Improve Glycemic Control and Endothelial Function in Subjects with Metabolic Syndrome

Abstract: Neem (Azadirachta indica) exhibits multiple therapeutic benefits in preclinical studies, but clinical studies are lacking. This clinical study investigated the efficacy and safety of an aqueous A. indica leaf and twig extract (NEEM) on metabolic parameters in subjects with metabolic syndrome (MetS). Subjects were randomized to receive (1) placebo or (2) 125 mg, (3) 250 mg, or (4) 500 mg of NEEM twice daily (n = 20/group) for 12 weeks. Fasting blood sugar (FBS) and insulin, postprandial blood sugar (PPBS), insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Several clinical and randomized control trials have successfully demonstrated the efficacy of neem extracts on gastric ulcer, 149 orodental protection, 150 psoriasis, 151 diabetic foot lesions, 152 metabolic syndrome, 153 and COVID‐19 9 . Although many preclinical studies have unequivocally demonstrated the cancer preventive and therapeutic potential of neem limonoids, clinical trials on these compounds have not been documented so far.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Several clinical and randomized control trials have successfully demonstrated the efficacy of neem extracts on gastric ulcer, 149 orodental protection, 150 psoriasis, 151 diabetic foot lesions, 152 metabolic syndrome, 153 and COVID‐19 9 . Although many preclinical studies have unequivocally demonstrated the cancer preventive and therapeutic potential of neem limonoids, clinical trials on these compounds have not been documented so far.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Conversely, nutritional interventions possess attributes such as minimal side effects, sustained efficacy, broad applicability, and cost-effectiveness, thereby assuming a pivotal role. Presently, nutritional interventions targeting insulin resistance center on dietary patterns [ 4 , 5 , 6 , 7 , 8 ], plant-derived compounds [ 9 , 10 , 11 , 12 , 13 ], probiotics [ 14 , 15 , 16 ], and other modalities. Nevertheless, many of these compounds predominantly exert singular effects.…”
Section: Introductionmentioning
confidence: 99%